Analisis faktor-faktor yang mempengaruhi permintaan kain batik Jambi di Kelurahan Mayang Mangurai Kecamatan Alam Barajo Kota Jambi - Anisa Dinda Lestari; Zulfanetti Zulfanetti; Hardiani Hardiani (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
The purpose of this study was (1) to analyze consumer characteristics of Jambi batik cloth based on the amount of demand for Jambi batik cloth in Mayang Mangurai Village, Alam Barajo District, Jambi City (2) to analyze the effect of Jambi batik cloth prices, consumer income, and prices of substitute goods on cloth demand. Jambi batik in Mayang Mangurai Village, Alam Barajo District, Jambi City. The method used in this study is a survey method using primary data obtained from questionnaires and direct interviews. The data analysis method used was descriptive and quantitative analysis methods with multiple linear regression analysis. The results of the study indicate that (1) the average age of consumers of Jambi batik cloth in Mayang Mangurai Village is 42 years, the last education average of Jambi batik cloth consumers is S1, the average job of Jambi batik cloth consumers is as a civil servant, the average consumer of Jambi batik cloth has a family of 4 people, and the average income earned by consumers of Jambi batik cloth is Rp.4.240.000 on average per month in a year; and (2) simultaneously and partially independent variables, the price of Jambi batik cloth, consumer income and the price of substitute goods have a significant effect on the demand for Jambi batik cloth in Mayang Mangurai Village, Alam Barajo District, Jambi City. Keywords: Demand, Price, Income, Price of Substitute Goods